Evaluation of Organic Amendments Against Ralstonia solanacearum Causing Bacterial Wilt in Ginger - Singh, Roop; Jagtap, G. P.; R. K, Bannihatti; Jatwa, T. K.; Khan, Irfan; Meena, Neeraj Kumar (International Journal of Bio-resource and Stress Management, 2017)
The present field study was undertaken to investigate the effective organic amendments against Ralstonia solanacearum under pot culture condition. The average (PESR+PESM) reduction in mortality recorded with all the organic amendments tested were ranged from 15.39 to 64.97% over untreated control. However, significantly highest reduction in average mortality was recorded with karanj cake (64.97%). This was followed by the organic amendments viz.,neem seed cake (43.95%), farm yard manure (37.36%), vermicompost (32.95%), poultry manure (32.24%) and sunflower seed cake (26.87%). Whereas, safflower seed cake (21.40%), goat manure (19.28%), cotton seed cake (18.60%) and groundnut cake (15.39%) were found less effective. All the test amendments improve root length, shoot length and vigour index in ginger. Among the different amendments tested, significantly highest root length (6.16 cm), shoot length (12.56 cm) and vigour index (1372.73) were recorded with Karanj cake. The second best amendment found was neem seed cake (5.26 cm, 10.26 cm and 931.20) respectively. This was followed by the amendments viz., farm yard manure (4.76 cm, 8.83 cm and 679.50), vermicompost (4.25 cm, 8.23 cm and 582.44), poultry manure (4.23 cm, 6.56 cm and 467.53), sunflower seed cake (4.08 cm, 6.13 cm and 374.40), safflower seed cake (3.66 cm, 5.96 cm and 352.76) for root length, shoot length and vigour index respectively.